Chapter Writing for the wor(l)ds: the reflection on language in Yiyun Li's literary production - Prosperi, Martina Renata (Studi e saggi, 2023)
Yiyun Li, b. 1972, moved from Beijing to the US in 1996, where she soon realized to be a talented writer. Although her early works, including the collections of short stories A Thousand Years of Good Prayers (2005) and Gold Boy, Emerald Girl (2010), and the novels The Vagrants (2009) and Kinder Than Solitude (2014), still privileged Chinese settings and characters, after the publication of her memoir Dear Friend, from My Life I Write to You in Your Life (2017) the literary landscape depicted by Li was amplified with autobiographical anecdotes and reflections on literature, human relations and language. Building upon psychoanalytical hints, this article offers a close reading of Where Reasons End (2019) and Must I Go (2020), reflecting on Li's literature from a global perspective, and arguing that her contribution to world literature lies in her bold dissociation from any conventional, crystallized and thus imprisoning use of language.